Mathematics Problem Solving Skill in ARIAS Learning with Scaffolding Strategy Viewed from Adversity Quotient based on Gender - Wicaksono, Dhanang Bayu; Waluya, S. B.; Sri Noor Asih, Tri (Unnes Journal of Mathematics Education Research, 2021)
This research aims to describe mathematics problem solving skill seen from adversity quotient based on gender of VIII graders. This mixed – method used sequential explanatory design. The population was taken from VIII graders of 11 Semarang, consisting of seven classes. The techniques of collecting data was purposive sampling. The findings showed that adversity quotient of the students were varied. They were shown from 10 high adversity quotient students consisting of 6 high mathematics problem solving skilled students and 4 moderate skilled students. From 17 students with moderate adversity quotient, 6 of them had high mathematics problem solving skills, 9 moderate skilled students, and 2 poor skilled students. From 5 students with poor adversity quotient, one of them had high mathematics problem solving skill, 2 moderate skill, and 2 poor skill students. Female students had higher mathematics problem solving skill than the male students. Female students also could re-check again their answers with different ways while male students could re-check with the same ways on high problem solving skill category.